Efektivitas Fermentasi Saccharomyces Cerevisiae dalam Media Gula Larut terhadap Volume Gas Karbon Dioksida yang dihasilkan: (Studi Eksperimen Menggunakan Balon sebagai Indikator di MI Jamiyatul Mubtadiin) - Intan Nur Laila; Muhammad Suwignyo Prayogo; Iklila Muzayyanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine how effective the fermentation process is carried out by the microorganism Saccharomyces cerevisiae in a soluble sugar medium, and how the sugar concentration affects the volume of carbon dioxide gas produced. The fermentation process was observed using a balloon as a simple indicator to measure the gas produced. The study was conducted with an experimental approach at MI Jamiyatul Mubtadiin, using three variations of sugar concentration: 10%, 15%, and 20%. The results showed that the higher the sugar concentration, the more carbon dioxide gas was formed. This shows that S. cerevisiae is able to utilize sugar efficiently to produce gas in the fermentation process. In addition to providing scientific understanding, this study is also associated with legal, religious, and philosophical values, thus providing a broader perspective on the application of fermentation in everyday life and education.